Dysfunctional families and crime: righting wrongs - Kamaruddin, Zaleha (2010)
There is a growing trend of our youths involving in crimes and showing disrespect for the law. What is more worrying is the rise of violent crimes committed by them. In the Malaysian context, this fact is confirmed by our newly-appointed Inspector General of Police, Tan Sri Ismail Omar when he took office this year. Many community leaders from all over the world have also raised their worry and concern as well. These concerns need to be addressed seriously. Pertinent questions need to be answered to understand reasons behind the phenomenon, i.e. why are our youths behaving this way? Why are they putting their future in jeopardy? How can we make these wrongs right? This paper will attempt to shed some light on these questions. It is divided into three parts: The first part will define dysfunctional families and its relationship with crime and some home-truths relating to them. Part two will emphasize the importance of knowledge and the inculcation of good values to individuals through the family. The final part of this paper deals directly with the situation where recommendations are made.